2021
DOI: 10.21203/rs.3.rs-407860/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimizing Stereotactic Radiosurgery in Patients With Recurrent or Residual Craniopharyngiomas

Abstract: PurposeStereotactic radiosurgery (SRS) is an important management strategy for residual and recurrent Craniopharyngiomas. The current study evaluated the factors which affected tumor control and complications in craniopharyngioma SRS.MethodsThis study includes 53 consecutive patients who underwent single-session SRS for recurrent or residual craniopharyngiomas. The median age was 41 years with 28 male and 25 females. The median tumor volume was 0.63 cm3 and median margin dose was 12 Gy (range, 9-25 Gy).Results… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
(9 reference statements)
1
4
0
Order By: Relevance
“…In that study, almost half of the patients had a tumor recurrence, resulting in treatment failure during the long-term period due to the reduced marginal dose of ≤10 Gy when the tumors adhered to the optic apparatus. Similar outcomes were reported in other studies in which higher margin dose (≥12 Gy) enables better local tumor control, [20] but sufficient distance to the optic nerve (≥2 mm, ≥3 mm or 3-5 mm) [6,7,19,20] is necessary to achieve that.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In that study, almost half of the patients had a tumor recurrence, resulting in treatment failure during the long-term period due to the reduced marginal dose of ≤10 Gy when the tumors adhered to the optic apparatus. Similar outcomes were reported in other studies in which higher margin dose (≥12 Gy) enables better local tumor control, [20] but sufficient distance to the optic nerve (≥2 mm, ≥3 mm or 3-5 mm) [6,7,19,20] is necessary to achieve that.…”
Section: Discussionsupporting
confidence: 85%
“…GKS has been reported to be an effective management option and studies have suggested 5-year progression-free survival rate of 72.1-90.3%. [4,16,20,26] However, these studies focused on one treatment and the comparison of outcomes from other radiation strategies and criteria for selecting treatment plans have not been established. GKS was mainly performed in a single fraction and it can threaten visual function when the tumor was touching or compressing the optic nerve.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As technology progresses, new techniques for management of craniopharyngioma will evolve as well. This increase in treatment options will likely result in expansion of multidisciplinary management of this tumor, especially with the evolution of other techniques such as stereotactic radiosurgery, which can be used as an adjunct to surgery or in patients unwilling or unable to undergo surgery [52][53][54]. For those patients unable to tolerate surgery, cysto-ventricular catheter placement has also been explored as an option to improve mass effect on optic pathways by using minimally invasive methods to stereotactically place catheters that connect cystic craniopharyngiomas to the ventricular system for drainage [55].…”
Section: Advances and Alternative Treatment Optionsmentioning
confidence: 99%